1999
DOI: 10.1021/js9900102
|View full text |Cite
|
Sign up to set email alerts
|

Role of an isomorphic desolvate in dissolution failures of an erythromycin tablet formulation

Abstract: The investigation of dissolution failures for erythromycin dihydrate tablet formulation over a 12-month period using a near-infrared spectroscopy technique revealed the role of a desolvated dihydrate in the retardation of dissolution. Near infrared spectroscopy (NIR) indicated a dehydrated dihydrate of erythromycin is produced during formulation and gradually binds with Mg(OH)2. The binding delays the process of dissolution. NIR was used to successfully predict that humidifying the tablets would reverse the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…A number of studies on these forms have been reported. [4][5][6][7][8][9][10][11] At the same time, a literature review showed that similar information on commercially marketed lots of Em raw material is often lacking, and significant variations in the physical properties of the bulk drug are encountered among material supplied by some manufacturers and among different lots supplied by the same manufacturer. 6 Additionally, the intricate molecular structure of Em (Figure 1) suggests the variety of possible supramolecular motifs in crystals, resulting in the formation of different polymorphic modifications.…”
Section: -3mentioning
confidence: 99%
“…A number of studies on these forms have been reported. [4][5][6][7][8][9][10][11] At the same time, a literature review showed that similar information on commercially marketed lots of Em raw material is often lacking, and significant variations in the physical properties of the bulk drug are encountered among material supplied by some manufacturers and among different lots supplied by the same manufacturer. 6 Additionally, the intricate molecular structure of Em (Figure 1) suggests the variety of possible supramolecular motifs in crystals, resulting in the formation of different polymorphic modifications.…”
Section: -3mentioning
confidence: 99%
“…5 Furthermore, the structural cavities created in a crystal of erythromycin A dihydrate upon water loss during formulation tend to be filled with excipient molecules of magnesium hydroxide, so that the final product fails the dissolution test. 19 Hence, the development of process analytical tools to ensure the appropriate solid state of the drug is clearly requested.…”
Section: Introductionmentioning
confidence: 99%
“…These results also indicate the relative reactivity of the 2 anhydrates to moisture, which has implications for form selection in product development. 23 The importance in differentiating between the desolvate and the anhydrate is also emphasized by the moisture sorption analysis shown in this study. A schematic representation of the behavior of niclosamide, with respect to solvents and RH, is shown in Figure 6.…”
Section: Discussionmentioning
confidence: 62%